Adipokines in gestational diabetes - Łopuszyńska, Anna Małgorzata; Ochyra, Łukasz; Pawlicki, Mateusz; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2022)
Introduction: Gestational diabetes (GDM) is any hyperglycemic condition that has appeared for the first time in previously healthy pregnant women. The incidence varies from 1% to 20% and is constantly increasing. GDM results in numerous complications for both the fetus and the mother. Adipokines are a group of protein hormones and cytokines that are secreted by adipose tissue. They affect glucose and lipid metabolism, insulin sensitivity, appetite, and immune response. Due to their involvement in these processes, there are more and more reports that adipokines influence the pathomechanism of gestational diabetes. Material and methods, aim: The literature in the PubMed scientific database published in 2015-2022 was searched using the keywords: gestational diabetes, adipokines. The aim of this review is to present the role of adipokines in the pathomechanism of gestational diabetes as well as their potential role in the detection and treatment of this condition. Results: The pathophysiology of gestational diabetes is not fully understood. It has been noted that mothers with GDM have elevated levels of leptin. In turn, the level of adiponectin is lower in women with gestational diabetes compared to healthy women. Adipokines such as visphatin, resistin or chimerin are also suspected of a possible role in the pathomechanism of the disease. These reports could lead to the discovery of a biomarker for the rapid detection of GDM. Conclusions: Gestational diabetes is a common disease in pregnancy, the incidence of which is constantly increasing. Its complications are dangerous for both the mother and her baby. That is why research is important that will allow us to learn about its pathomechanism, to detect it faster, and to prevent it. Studies using adipokines show promising results, hence the urgent need for more randomized, multicentre studies to better understand their role in gestational diabetes.